2014
DOI: 10.1097/brs.0000000000000606
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Complications After Anterior Cervical Discectomy and Fusion in the Elderly

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 34 publications
5
35
1
Order By: Relevance
“…The overall incidence of wound complications was lower than the reported 3.5% observed in a similarly structured NSQIP study on pediatric patients. 16 Since increasing age has been previously reported as a predictor for postoperative complications, 38 a higher rate of wound infection was expected. However, it is important to consider that the incidence varied from 2.0% to 4.1% within the NSQIP database for adults, and the pediatric article reported data from a single year.…”
Section: Discussionmentioning
confidence: 98%
“…The overall incidence of wound complications was lower than the reported 3.5% observed in a similarly structured NSQIP study on pediatric patients. 16 Since increasing age has been previously reported as a predictor for postoperative complications, 38 a higher rate of wound infection was expected. However, it is important to consider that the incidence varied from 2.0% to 4.1% within the NSQIP database for adults, and the pediatric article reported data from a single year.…”
Section: Discussionmentioning
confidence: 98%
“… 20 - 22 Carreon et al 5 found in an analysis of elderly patients undergoing lumbar decompression and arthrodesis that patients ≥75 years of age had a 1.6-day longer LOS compared with patients aged 65 to 69 years (9.3 vs 10.9 days). 5 Additionally, in a retrospective analysis of 6,253 patients undergoing ACDF, Buerba et al 23 identified patients 65 to 74 years old experienced a 1.59 greater odds of LOS ≥3 days and patients >75 years old experienced a 2.50 greater odds of LOS ≥3 days. Patients ≥61 years of age were more than 3 times as likely to experience pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…Age was stratified into three groups-18 to 64, 65 to 74, !75-as 65 is a standard cutoff in the literature 62,63 and 75 is one SD above the mean for our dataset. 64 Clinical descriptors included preoperative functional status, presence of system-specific and general comorbidities, and ASA score. Comorbidities were coded by system for cardiac (angina, congestive heart failure, myocardial infarction, previous percutaneous coronary intervention or cardiac surgery, peripheral vascular disease, stroke, or transient ischemia attack) and respiratory (chronic obstructive pulmonary disease, dyspnea, pneumonia) disorders.…”
Section: Assessments and Outcome Measuresmentioning
confidence: 99%